(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2023)
The paper is a continuation of the previously published paper for the Yearbook of the Faculty of Law in Stip from 2019, and it refers to Regulation 2017/1939 and the establishment of the European Public Prosecutor’s Office (EPPO). In the paper, the authors partially elaborate the functioning of the EPPO, by giving a special emphasis of the judicial review of the investigative measures taken by the EPPO. After a brief explanation of the structure and competence of the KEJO, the authors provide a brief insight into the implementation of the Regulation in the countries of the region, and than approaching the key part of the paper, which is the judicial review of the measures taken by the EPPO. The main part of the paper analyzes the first question referred to the Court of Justice of the European Union (CJEU) in the preliminary ruling procedure about the interpretation of the key provision regarding the investigations of the EPPO, in accordance with Article 31 of the Regulation. This provision regulates investigative measures to be taken in a member-state other than the member-state in which the European Delegated Prosecutor is acting. In the specific case, the High Court of Austria refers questions to the CJEU in a preliminary ruling procedure, seeking clarification on the degree of judicial review when it comes to cross-border investigations within this regime. According to the authors, the case raises a number of key questions regarding the structure and functioning of the EPPO, as well as regarding the relevance of the EPPO in the creation of a common area of justice in the EU. In the conclusion, the authors refer to several procedural challenges on which the judgment of the CJEU may depend and on which the future functioning of the EPPO and the eventual revision of the Regulation itself may depend.